Diastolic Blood Pressure and Intensive Blood Pressure Control on Cognitive Outcomes: Insights From the SPRINT MIND Trial. Issue 3 (23rd January 2023) - Jiang, Chao; Li, Sitong; Wang, Yufeng; Lai, Yiwei; Bai, Yu; Zhao, Manlin; He, Liu; Kong, Yu; Guo, Xueyuan; Li, Songnan; Liu, Nian; Jiang, Chenxi; et al.
Abstract : Background: The potential benefits or harms of intensive systolic blood pressure (BP) control on cognitive function and cerebral blood flow in individuals with low diastolic blood pressure (DBP) remain unclear. Methods: We conducted a post hoc analysis of the SPRINT MIND (Systolic Blood Pressure Intervention Trial Memory and Cognition in Decreased Hypertension) that randomly assigned hypertensive participants to an intensive (<120 mm Hg; n=4278) or standard (<140 mm Hg; n=4385) systolic blood pressure target. We evaluated the effects of BP intervention on cognitive outcomes and cerebral blood flow across baseline DBP quartiles. Results: Participants in the intensive group had a lower incidence rate of probable dementia or mild cognitive impairment than those in the standard group, regardless of DBP quartiles. The hazard ratio of intensive versus standard target for probable dementia or mild cognitive impairment was 0.91 (95% CI, 0.73–1.12) in the lowest DBP quartile and 0.70 (95% CI, 0.48–1.02) in the highest DBP quartile, respectively, with an interaction P value of 0.24. Similar results were found for probable dementia (interaction P =0.06) and mild cognitive impairment (interaction P =0.80). The effect of intensive treatment on cerebral blood flow was not modified by baseline DBP either (interaction P =0.25). Even among participants within the lowest DBP quartile, intensive versus standard BP treatment resulted in an increasing trend of annualized change in cerebral blood flow (+0.26 [95% CI, −0.72 to 1.24] mL/[100 g·min]). Conclusions: Intensive BP control did not appear to have a detrimental effect on cognitive outcomes and cerebral perfusion in patients with low baseline DBP. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01206062